Handling Complaints Against Revisit Intentions Through Satisfaction in Handling Guest Complaints at Hotel Artotel Thamrin Jakarta - Linda Desafitri RB; Vienna Artina (Greenation International Journal of Tourism and Management, 2024)
The handling of guest complaints must be simplified both in the process of handling, the method and time of handling the complaint where the purpose of the complaint on the guest's complaint can function as a source of service improvement in the future and good handling of customer complaints determines the customer's attitude in experiencing the quality of service which has an impact on the intention of returning guests in the future. The results of this study obtained the results that: (1) Handling Complaint directly has a significant influence on Satisfaction with Handling Complaint; (2) Handling Complaints directly has a significant influence on the Revisit Intention; (3) Satisfaction with Handling Complaint directly has a significant influence on the Revisit intention and (4) Indirectly there is a significant influence between Handling Complaint on the Revisit intention and through Satisfaction with Handling Complaint.